“With a Little Help from my Friends”: Exploring Pseudo-Social Music Listening Experiences - Scott Bannister; Freya Bailes; Alinka E. Greasley (Music & Science, 2025)
Contemporary research highlights intimate connections between music and social bonding, such that even modern music listening behaviors, including listening when alone, may be social experiences; in some cases, music may behave as a social “agent” with which interpersonal or social experiences can occur for listeners. However, these types of experiences, labeled here as pseudo-social music listening ( P-SML ) experiences, have rarely been investigated directly. This paper outlines a preliminary study of P-SML experiences, exploring six conceptual types of experience identified in existing literature ( Company , Consolation , Empathy , Personas and Narratives , Identification , and Feeling One with music). Through a questionnaire containing rating scale and open-ended questions, participants ( N  = 117) highlighted how relatable these six proposed P-SML types were to their own listening experiences, by ranking vignette statements describing the experiences of other listeners. Participants then recalled a P-SML experience of their own, describing their subjective feelings, qualities of the music involved, and whether this experience is consistent or situation-dependent. Results suggest that participants often described P-SML experiences as emotional experiences that involve a felt sense of connection or resonance between listener and music. Factors considered important for P-SML experiences include the emotional expression of the music, melodies and harmonies, and rhythm. Extra-musical knowledge, such as knowledge of the composer, songwriter, or performer, was considered less important. Findings are discussed in terms of links between music, emotion and social bonding, conceptualizing connection and resonance when listening to music in relation to parasocial interactions, and refining a conceptual foundation of P-SML experiences for future work.